Poor Embryo Quality Is Associated With A Higher Risk of Low Birthweight in Vitrified-Warmed Single Embryo Transfer Cycles - Huang, Jiaan; Tao, Yu; Zhang, Jie; Yang, Xiaoyan; Wu, Jiayi; Kuang, Yanping; Wang, Yun (Frontiers in Physiology, 2020)
Background: Previous studies have reported the association between embryo quality and perinatal outcome in fresh cycles, after cleavage-stage or blastocyst embryo transfer, and found no significant difference. However, in terms of vitrified-warmed embryo transfer cycles, the impact of embryo quality on the neonatal and maternal outcome has not been evaluated. Objectives: To explore whether the quality of a single vitrified-warmed embryo has an effect on the neonatal and maternal outcomes. Methods: 2403 infertile women undergoing single vitrified-warmed embryo transfer from January 2006 to July 2018 who had a live-born singleton delivered. Neonatal and maternal outcomes were compared between singletons resulting from the use of single good quality embryo (GQE) (n=1854) and single poor quality embryo (PQE) (n=549) and analyzed in the group of cleavage-stage embryo transfer and the group of blastocyst transfer, respectively. Results: A significantly higher risk of low birthweight (LBW, birthweight <2500g) was observed in the singletons derived from the transfer of single PQE compared with those derived from the transfer of single GQE both in cleavage and blastocyst stage (cleavage-stage, AOR 2.62, 95% CI 1.27-5.37; blastocyst stage, AOR 1.98, 95% CI 1.06-3.70). An increased risk of preterm birth (PTB, gestational age <37 weeks) was also observed in singletons born after transfer of a PQE of cleavage-stage compared with those after a GQE of cleavage-stage (AOR 2.40, 95% CI 1.28-4.49). The transfer of single poor quality blastocyst was associated with a higher risk of placenta previa compared with the transfer of single good quality blastocyst (AOR 2.65, 95% CI 1.26-5.57). Other maternal complications, neonatal malformations and neonatal complications were similar between compared groups. Conclusions: In vitrified-warmed cycles with single embryo transfer (SET), poor embryo quality would resulted in significant higher risk of LBW, regardless of cleavage-stage or blastocyst embryo transfer. Meanwhile, the transfer of poor cleavage-stage embryo was also associated with increased incidence of PTB.